Linking Changes in Inequality in Life Expectancy and Mortality: Evidence from Denmark and the United States - Gordon B. Dahl; Claus Thustrup Kreiner; Torben Helen Nielsen; Benjamin Ly Serena (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We decompose changing gaps in life expectancy between rich and poor into differential changes in age-specific mortality rates and differences in “survivability”. Declining age-specific mortality rates increases life expectancy, but the gain is small if the likelihood of living to this age is small (ex ante survivability) or if the expected remaining lifetime is short (ex post survivability). Lower survivability of the poor explains half of the recent rise in life expectancy inequality in the US and the entire rise in Denmark. Cardiovascular mortality declines favored the poor, but differences in lifestyle-related survivability led inequality to rise.
Keywords: I14; 330; life expectancy inequality; mortality inequality